PENGGUNAAN KARTU DOMINO MATEMATIKA DALAM FRAMEWORK ELPSA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Akbar, Khairul (Universitas Pendidikan Mandalika (UNDIKMA), 2018)
This study aims to improve student learning outcomes on material eksponensial using mathematical dominoes in the ELPSA framework. This research is a classroom action research (CAR) conducted in two cycles. The subjects of this study were students IX-1 grade of Â SMPN 2 Praya Barat Daya, Central Lombok District TP. 2017/2018 there were 28 people consisting of 15 female students and 13 male students. The research data collection instruments were Observation Sheet and Test Sheet. Indicators of research success are determined based on KKM 70 as a determinant of individual completeness with Classical Completion (KK) of 70%. The results showed that the average pre-action learning achievement was 30.71. After the action in the first cycle increased to 60.18. Student learning achievements in the first cycle increased by 29.47. In the second cycle the average student learning achievement was 76.07, which means an increase of 15.89 from the first cycle. Mastery learning / classical completeness in pre-action by 14.29% increased in the first cycle to 42.86%, and also increased in the second cycle by 71.43%. From the results of this study it can be concluded that the use of mathematical dominoes in the ELPSA framework on material eksponensial can improve student learning outcomes.